2015
DOI: 10.5603/cj.a2014.0089
|View full text |Cite
|
Sign up to set email alerts
|

A new score system for predicting response to cardiac resynchronization therapy

Abstract: 06%). A 4-point score system was generated based on tricuspid annular plane systolic excursion (TAPSE), longitudinal strain (LS), and complete left bundle branch block (CLBBB)combined with a wide QRS duration (QRSd). The sensitivity and specificity for prediction of a positive response to CRT at a score > 2 were 0.823 and 0.850, respectively (AUC: 0.92295% CI 0.691-0.916, p< 0.001). Conclusions: A patient selection score system based on the integration of TAPSE, LS and CLBBB combined with a wide QRSd can help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…Kang Y et al [21] observed, that longitudinal strain and LBBB combined with a wide QRS can help to predict positive response to CRT effectively and reliably. In another study, none of the longitudinal strain indices was different between echocardiographic responders and nonresponders to CRT [22].…”
Section: Discussionmentioning
confidence: 99%
“…Kang Y et al [21] observed, that longitudinal strain and LBBB combined with a wide QRS can help to predict positive response to CRT effectively and reliably. In another study, none of the longitudinal strain indices was different between echocardiographic responders and nonresponders to CRT [22].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Japan Cardiac Device Treatment Registry (JCDTR) database [21], the proportion of HF patients with NICM is as great as 70%. Based on our previous studies, patients with NICM were also common (> 60%)in China [6,22].…”
Section: The Published Scoresmentioning
confidence: 93%
“…9,10,21) This finding is also practical in clinical situations because a 12-lead ECG is available for every patient before CRT and provides a reasonable sensitivity and specificity in predicting the response to CRT. Although some other tools are also available for predicting outcome after CRT, such as echocardiography including the tissue Doppler technique, 22) cardiovascular magnetic resonance, 23,24) and nomograms, 3,22,25,26) QRS duration and complete LBBB on a surface ECG are still the proven independent predictors for the response after CRT. 3,27) In the present study, the shortest, longest, and average QRS durations were significantly different.…”
Section: Discussionmentioning
confidence: 99%